Idea generation and integration method for inclusion and integration teamwork - Cañizares, Juan Carlos Márquez; Rojas, Juan-Carlos; Acuña, Alejandro (Frontiers in Education, 2023)
Idea generation is fundamental in higher education, principally in engineering and creative areas. The challenge presented in our research was to correctly implement a progressive, intuitive categorization method to generate solutions, unifying individual proposals and ideas through a virtual platform or face-to-face sessions and real-time communication. This paper aims to present the implementation impact from students' first-use perceptions and experiences, segmented by study area, gender, and semesters. Our research began with creating an idea generation method. Experienced design professionals integrated various tools to run on digital platforms. This method was called ICRI, an acronym for Ideation, Categorization, Regrouping, and Ideation. The method had two primary stages. The initial stage employed four-step where the students defined, investigated, established findings, and formed teams to move on to the second stage. This second stage comprised two parts, the first four-step where students generated ideas, reviewed, defined, and grouped them; the second five-step process involved focusing the ideas for regrouping, discussion, fusion, and writing new ideas. This method was applied to start a product design process or design strategy to create a project design. The results revealed high student acceptance of the method due to its practicality, rapidity, and functionality in generating ideas and active, equitable student participation. We found that certain students' profiles are not optimistic about the use of such tools. Also, we found that there were no significant differences by gender of the student profile, but it was noted that female students liked the method more. The findings derived from the creation and application of the ICRI method were consequences of the need to create innovative practices to integrate higher education students. The ICRI method reinforces the trend of educational methods that address the relevance of collaborative idea generation and processes that facilitate effective interactions, even in a virtual and remote mode.